The Involvement of Indonesian Civil Society Organizations in the Policy-Making Process of Migrant Workers Protection in ASEAN - Iyan Septiyana (Journal of Indonesian Social Sciences and Humanities, 2019)
Indonesia is biggest sending country of migrant worker in the region. half of the number of Indonesian worker is undocumented migrant workers that vulnerable to be a victim of worker rights or human rights violation. The absent of regional policy of migrant worker protection in ASEAN, makes the issue get less attention in ASEAN multilateral framework. Then in 2007 the first regional policy of migrant worker appeared in ASEAN, in the process it involves CSOs from all ASEAN member states. While ASEAN itself is regional organization that conduct state-centric system which position state as a leading actor. This condition bring up a question how the involvement of Indonesian CSO in the policy-making process of migrant workers protection in ASEAN. Through the perspective of critical theory of Habermas, there is a space in the public sphere that can be used by CSO to emancipate migrant workers by conducting dialogue by establish and join network that is HRWG and TFAMW, then CSO can involves in the ASEAN policy making process of migrant workers protection.